Connecting Spiritual Rational Humanism: The Trend of Religious Moderation in the Modernization of Madrasah - Sri Bulan; M. Yunus Abu Bakar; Ah. Zakki Fuad; Hikmawati Rahayu (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The rapid intellectual development of Islam in Indonesia has necessitated the modernization of Islamic education, particularly in Madrasah Aliyah Negeri (MAN/ Public Islamic High School) Insan Cendekia Pekalongan, which integrates spiritual rational humanism with religious moderation. This study examines the connection between religious values and rational modernization through the transformation of five core programs: digital madrasah, foreign language development, adiwiyata madrasah, research madrasah, and homestay programs. Employing a qualitative field research method, data was collected through in-depth interactive communication with key stakeholders, including the head of the madrasah, deputy heads, and research supervisors. The findings reveal that the rational-spiritual connection is manifested through program modernization, which integrates multicultural values, tolerance, and local wisdom into the madrasah’s academic environment. The modernization framework is inspired by Habibie's intellectual and technological advancements, aiming to cultivate holistic human development through the synergy of faith, science, and technology. This study highlights the strategic role of religious moderation in balancing Islamic spirituality and rational thought, enabling students to navigate contemporary educational challenges while maintaining their cultural and religious identity. The implications of this research underscore the necessity of curriculum transformation in Islamic education to enhance scientific literacy, critical thinking, and social intelligence, thereby fostering a generation of Muslim scholars and professionals who embody intellectual and ethical excellence. Future studies should explore the longitudinal impact of these modernization programs on students' academic and socio-religious trajectories.